2008
DOI: 10.1021/cg701133b
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Evolution of Sb2S3 under Hydrothermal Conditions: Flowerlike Structure to Nanorods

Abstract: Nanorods of Sb 2 S 3 have been synthesized by a surfactant assisted hydrothermal method. The formation of nanorods through flowerlike morphology with an intermediate straw tide like structure has been depicted by scanning electron microscopy (SEM) study. This type of observation is the first of its kind for this material, and it has been explained on the basis of a two step heterogeneous nucleation-growth mechanism followed by crystal splitting. Raman spectroscopy of the nanorods has been carried out to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 25 publications
14
36
0
1
Order By: Relevance
“…Some elongated particles and particle aggregates were also present. Similar results about the shape of stibnite synthesized by sonochemical method also were data but the small particles were found 6 . It has been known that there are two regions of sonochemical activity.…”
Section: Stibnite Characterizationsupporting
confidence: 81%
See 1 more Smart Citation
“…Some elongated particles and particle aggregates were also present. Similar results about the shape of stibnite synthesized by sonochemical method also were data but the small particles were found 6 . It has been known that there are two regions of sonochemical activity.…”
Section: Stibnite Characterizationsupporting
confidence: 81%
“…In the mean time, there already exist a number of reports toward synthesis of nanorods of stibnite. So far, various synthetic methods such as hydrothermal [5][6][7] , and complexing agent assisted 8 have been employed to synthesize this material either in rod, ribbon or wire form. Sonochemical processing has been proven to be an useful technique for generating stibnite nanorods under ambient air from an ethanolic solution containing antimony trichloride and thioacetamide 8 .…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported for other sheaf-like crystals, including Bi 2 S 3 [16][17][18], -FeO(OH) [19], BaWO 4 [20,21], lanthanum orthovanadates [22], Sb 2 S 3 and Sb 2 Se 3 [23,24], CuO [25,26], CeO 2 [27] and Tb-doped CePO 4 [28], it has been widely accepted that the formation mechanism of sheaf-like morphologies is because of crystal splitting. Crystal splitting possibly occurs because of solution oversaturation conditions are used, or the presence of additives which may influence the crystal growth process leading to crystal splitting.…”
Section: Growth Mechanismsupporting
confidence: 52%
“…Qian et al found that a secondary nucleation could be observed on the top surface of the individual crystal [22]. In [17] and [18], people also found that Sb 2 S 3 crystals splitting occurred easily. With the help of surfactant, imperfect oriented attachment of nuclei appeared.…”
Section: Resultsmentioning
confidence: 99%